PEMODELAN SEMIVARIOGRAM EKSPERIMENTAL PADA JUMLAH PENYEBARAN PRODUKSI KELAPA SAWIT DI INDONESIA: Experimental Semivarogram Modeling On The Number Of Oil Palm Production Distribution in Indonesia - ilam Maryam; Tantri Julia Arsita; Hendy Stevanus; Ehairun Nisa (Fraction: Jurnal Teori dan Terapan Matematika, 2022)
Oil palm is a leading plantation commodity in Indonesia with the industrial distribution area covering Sumatra, Kalimantan, Sulawesi and surrounding areas. This study aims to model the semivarogram of the distribution of oil palm production in Indonesia. The data used in this study is secondary data obtained through the official website of the Indonesian Central Statistics Agency (BPS), in the form of data on oil palm production in 34 provinces in Indonesia from 2012 to 2021. The method used in this study is an experimental semivariogram method. , then fitting the model from five models, namely Exponential model, Spherical model, Gaussian model, Logarithmic model and Wave model (holt effect) by looking at the value of the Nugget effect (Co). Based on the discussion of the number of models that are suitable to see the highest palm oil production in Indonesia, the Wave (hol effect) model with a Nugget effect value of 0 and the foem of the equation is...*